Pengaruh Perkembangan Obligasi Ritel Indonesia Terhadap Laporan Keuangan PT. BNI (Persero) Tbk Tahun 2011-2015 - Sugiyanto Sugiyanto; Novie Dewi Kustiani (Accounthink, 2018)
This research objective is to know the Influence Of The Development Retail Bond Indonesia To The Financial Statment Of Pt Bank Negara Indonesia (Persero) Tbk Period 2011-2015 This research used quantitative methods. The data collection techniques used literature study. The sample was financial statements period of 2011-2015. Analytical techniques used normality data test, simple linear regression, correlations, determination coefficient, and hypotheses test Using SPSS version 19. The research result show balance of retail indonesia has a very strong influence on the financial statements of 0,931% by using pearson correlation. And the coefficient of determination of 86,7% shows the effect of retail bonds Indonesia to the financial statment while the remaining 7,67% can be influenced by other variable-variables. As for the problems that occur in  the influence of retail bonds Indonesia to the financial statements at the PT Bank Negara Indonesia (persero) tbk is the balance of bonds that fluctuate and financial statments decline in the period 2011. Suggestion from the authors for the company that should increase the return of investors in order to increase. Keywords : retail bond Indonesia, financial statment